2014
DOI: 10.1016/j.radonc.2014.08.033
|View full text |Cite
|
Sign up to set email alerts
|

A dosimetric comparison of proton and intensity modulated radiation therapy in pediatric rhabdomyosarcoma patients enrolled on a prospective phase II proton study

Abstract: Background Pediatric rhabdomyosarcoma (RMS) is highly curable, however, cure may come with significant radiation related toxicity in developing tissues. Proton therapy (PT) can spare excess dose to normal structures, potentially reducing the incidence of adverse effects. Methods Between 2005 and 2012, 54 patients were enrolled on a prospective multi-institutional phase II trial using PT in pediatric RMS. As part of the protocol, intensity modulated radiation therapy (IMRT) plans were generated for comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 41 publications
3
57
0
Order By: Relevance
“…The dosimetric advantage of PRT over X/E RT has been well documented in previous studies [21, 22]. The clinical benefit of PRT, however, is less clear.…”
Section: Discussionmentioning
confidence: 78%
“…The dosimetric advantage of PRT over X/E RT has been well documented in previous studies [21, 22]. The clinical benefit of PRT, however, is less clear.…”
Section: Discussionmentioning
confidence: 78%
“…3, 8-12 Proton radiotherapy can deliver less radiation dose to normal tissues than photon radiotherapy, because of the underlying physics intrinsic to its dose deposition and when compared with external beam photon techniques. 137, 14-16 Because of the dose sparing to normal tissues, it has been widely hypothesized that the lower radiation dose to normal tissue may reduce the incidence and/or severity of late effects. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Dosimetric comparison of IMRT to proton therapy treatment plans in a phase II trial of patients with pediatric rhabdomyosarcoma demonstrated the mean integral dose was 1.8 times higher for IMRT to the head and neck (p<0.01), and significant tissue sparing was seen in many critical structures such as chiasm, pituitary, hypothalamus, brainstem, cerebellum, maxilla, mandible, contralateral optic nerve, and temporal lobe with the use of protons. [7] Similarly, Kozak et al in a dosimetric comparison of IMRT and proton therapy for parameningeal rhabdomyosarcomas reported a significant decrease in mean dose in all normal structures except for ipsilateral cochlea and mastoid with proton radiotherapy. [13] Childs et al reported the late toxicities of proton radiation in 10 pediatric patients with parameningeal rhabdomyosarcoma including decreased height velocity, endocrinopathies, facial hypoplasia, chronic nasal congestion, and dental problems, with a median follow-up time of 5 years.…”
Section: Discussionmentioning
confidence: 91%
“…[4] In an effort to reduce radiation doses to normal tissue, and thereby minimize the acute and long-term toxicity of radiotherapy, radiation techniques for patients with head and neck rhabdomyosarcoma have significantly evolved over the past 20 years from three-dimensional (3D) conformal planning to IMRT and also proton radiotherapy. [4][5][6][7] While Paulino et al…”
Section: Introductionmentioning
confidence: 99%